2020
DOI: 10.1183/23120541.00172-2019
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nintedanib in a Greek multicentre idiopathic pulmonary fibrosis registry: a retrospective, observational, cohort study

Abstract: Nintedanib is a tyrosine kinase inhibitor approved for the treatment of idiopathic pulmonary fibrosis (IPF). In a retrospective, real-world study across seven Greek hospitals, we evaluated the effectiveness and safety of nintedanib in routine clinical practice. Patients diagnosed with IPF, as per guideline criteria or multidisciplinary diagnosis, received nintedanib between January 2013 and January 2018.We evaluated 244 patients: mean±sd age 71.8±7.5 years, 79.1% male, 45.1% current smokers and 33.1% ex-smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
54
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 36 publications
13
54
0
3
Order By: Relevance
“…On the basis of global pharmacovigilance data collected over 4 years, the safety profile of nintedanib in patients with IPF was consistent with that observed in clinical trials, with no new safety concerns observed. The most frequent adverse event reported in the global pharmacovigilance database was non-serious diarrhea, in line with observations from clinical trials [5,[11][12][13][14], observational studies conducted in clinical practice [15][16][17][18][19][20][21][22][23], and post-marketing surveillance data collected in the USA in the year following the approval of nintedanib as a treatment for IPF [24]. Nintedanib is an intracellular inhibitor of tyrosine kinases that inhibits processes fundamental to the pathogenesis of pulmonary fibrosis [9,10,25,26].…”
Section: Discussionsupporting
confidence: 57%
“…On the basis of global pharmacovigilance data collected over 4 years, the safety profile of nintedanib in patients with IPF was consistent with that observed in clinical trials, with no new safety concerns observed. The most frequent adverse event reported in the global pharmacovigilance database was non-serious diarrhea, in line with observations from clinical trials [5,[11][12][13][14], observational studies conducted in clinical practice [15][16][17][18][19][20][21][22][23], and post-marketing surveillance data collected in the USA in the year following the approval of nintedanib as a treatment for IPF [24]. Nintedanib is an intracellular inhibitor of tyrosine kinases that inhibits processes fundamental to the pathogenesis of pulmonary fibrosis [9,10,25,26].…”
Section: Discussionsupporting
confidence: 57%
“…Trials are based on drugs that are already approved for other diseases, have acceptable safety profiles or have been effective in animal studies against the other two highly pathogenic coronaviruses (30). Pirfenidone and nintedanib are the two approved antifibrotic drugs that, despite having different modes of action, are both effective in attenuating the rate of lung function decline and are widely considered to improve life expectancy (31,32). Apart from the potent use of antivirals to reduce the viral effects, the use of antifibrotic therapies could also be under consideration based on the pulmonary fibrotic disease observed after COVID-19 recovery (33).…”
Section: Is There a Role For Antifibrotic Therapy?mentioning
confidence: 99%
“…Many real world studies have been carried out since the licensing of these medications, which have shown the disease stabilising effect of these drugs through sequential FVC measurements [9][10][11][12][13][14]. These studies have also assessed anti brotic tolerability with the discontinuation rate for pirfenidone approximately 29% and for nintedanib between 11% and 19% [9,10,13,14].…”
Section: Introductionmentioning
confidence: 99%